Population-based study of incidence, risk factors, outcome, and prognosis of ischemic peripheral arterial events: implications for prevention - Howard, D; Banerjee, A; Fairhead, J; Hands, L; Silver, L; Rothwell, P (American Heart Association, 2015)
Background There are few published data on the incidence and long-term outcomes of critical limb ischemia, acute limb ischemia, or acute visceral ischemia with which to inform health service planning, to monitor prevention, and to enable risk prediction. Methods and Results In a prospective population-based study (Oxfordshire, UK; 2002–2012), we determined the incidence and outcome of all acute peripheral arterial events in a population of 92 728. Risk factors were assessed by comparison with the underlying population. A total of 510 acute events occurred in 386 patients requiring 803 interventions. Two hundred twenty-one patients (59.3%) were ≥75 years of age, and 98 (26.3%) were ≥85 years old. Two hundred thirty patients (62.3%) were independent before the event, but 270 (73.4%) were dead or dependent at the 6-month follow-up, and 328 (88.9%) were dead or dependent at 5 years. The 30-day survival was lowest for patients with acute visceral ischemia (28.2%) compared with acute limb ischemia (75.3%) and critical limb ischemia (92.6%; P<0.001). Risk factors (all P<0.001) were hypertension (age- and sex-adjusted risk ratio, 2.75; 95% confidence interval, 1.95–3.90), smoking (adjusted risk ratio, 2.14; 95% confidence interval, 1.37–3.34), and diabetes mellitus (adjusted risk ratio, 3.01; 95% confidence interval, 1.69–5.35), particularly for critical limb ischemia (adjusted risk ratio, 5.96; 95% confidence interval, 3.15–11.26). Two hundred eightyeight patients (77.2%) had known previous cardiovascular disease, and 361 (96.8%) had vascular risk factors, but only 203 (54.4%) were on an antiplatelet and only 166 (44.5%) were on a statin. Although 260 patients (69.7%) were taking antihypertensives, 42.9% of all blood pressures recorded during the 5 years before the event were >140/90 mm Hg. Of 88 patients (23.6%) with incident cardioembolic events, 62 had known atrial fibrillation (diagnosed before the event), of whom only 14.5% were anticoagulated despite 82.3% having a CHA2DS2 VASC score ≥2 without contraindications. Conclusions The clinical burden of peripheral arterial events is substantial. Although the vast majority of patients have known vascular disease in other territories and multiple treatable risk factors, premorbid control is poor.